Controllability, Observability and Stability of Volterra Type Non-Linear Matrix Integro-Dynamic System on Time Scales - V. Ramana, G; V. S. R. Deekshitulu, G (International Journal of Engineering and Technology, 2018)
This paper investigates the controllability, observability and stability of the solution of Volterra type non linear matrix integro dynamic system on time scales.Â Â